Evaluating Forces Associated with Sentient Drivers over the Purchase Intention of Organic Food Products - Kiran, Prabha; Srivastava , Abhishek; Tiwari, Satish Chandra; Ramaiah, T Sita (Asian Journal of Agriculture and Rural Development, 2020)
The study proposes to find out the factors which influence awareness among the consumers towards purchasing organic food product. The study is based on primary data by using tools Chi-square test, Cronbach alpha, KMO, and Bartlett’s test, ANOVA, regression, correlation, and cross-tabulation. The study found that awareness driver’s nutritional information, price, certification, brand name, and logos have an essential influence on the purchase intention of the product of organic food. However, labeling and food standards do not show a noteworthy rapport between labeling and organic food products’ purchase plans. The core commitment and flow to explore are to analyze purchasers with respect to organic guarantee systems (accreditation, guidelines, logo, imprints, and confirmation) so we can distinguish the genuine organic products. The independent factors of awareness like organic buying preference and buying frequency, have a significant influence on the purchase intention of organic food. The research provided evidence of consumer awareness and purchase intention of organic food that would help the organic food industry to promote their products according to the attribute of customers.